2018
DOI: 10.1021/acsomega.8b01787
|View full text |Cite
|
Sign up to set email alerts
|

New Strategy To Access Enantioenriched Cyclohexadienones: Kinetic Resolution of para-Quinols by Organocatalytic Thiol-Michael Addition Reactions

Abstract: Existing stereoselective routes to 2,5-cyclohexadienones involve either desymmetrization of an achiral substrate or have attempted to perform an asymmetric dearomatization of a phenol. Herein, we report proof-of-principle experiments aimed at developing a kinetic resolution as an alternative method for accessing enantioenriched 2,5-cyclohexadienones. More specifically, chiral bifunctional thiourea catalysts were used to promote the addition of 2-thionapthalene into unsymmetric para -quin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 87 publications
0
9
0
Order By: Relevance
“…After screening various catalysts, it was observed that catalyst 93 appeared to be the best which provided Michael addition to para ‐quinol 89 as a single diastereomer 91 and unreacted enantiomer of para ‐quinol 92 (Scheme 11). [48] …”
Section: Asymmetric Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…After screening various catalysts, it was observed that catalyst 93 appeared to be the best which provided Michael addition to para ‐quinol 89 as a single diastereomer 91 and unreacted enantiomer of para ‐quinol 92 (Scheme 11). [48] …”
Section: Asymmetric Synthesismentioning
confidence: 99%
“…After screening various catalysts, it was observed that catalyst 93 appeared to be the best which provided Michael addition to para-quinol 89 as a single diastereomer 91 and unreacted enantiomer of para-quinol 92 (Scheme 11). [48] Tian and co-workers developed a method of kinetic resolution of nonactivated terminal alkene-tethered 2,5-cyclohexadienone 94 with rhodium (III)-catalyst 98. Bis (pinacolato) diboron (B 2 pin 2 ) 95, promoted asymmetric borylative cyclization of compound 94, provided recovered cyclohexadienone 96 and cis-hydrobenzofuranone 97 with excellent yield and enantioselectivity (up to 99 % ee).…”
Section: Through Kinetic Resolutionmentioning
confidence: 99%
“…Reaction rates can be markedly enhanced by substitution at the phenyl moiety: Trifluoromethyl substitution of diphenylthiourea greatly enhances reaction rates and yields. , This enhancement has been primarily ascribed to electronic effects as the electron-withdrawing trifluoromethyl groups increase the acidity of the N–H groups, , enhance π–π interactions, , and enhance the polarity of the ortho-protons of the phenyl ring . Additionally, the choice of the solvent can affect catalytic efficiency . Yet, substitution at the phenyl ring (e.g., trifluoromethyl) and solvents can also affect conformational equilibria and thereby affect catalytic activity. …”
Section: Introductionmentioning
confidence: 99%
“…Kinetic resolution as one, which converts racemic dienone into an enantiomerically enriched product and recovered chiral non-racemic cyclohexadienone (Figure 2a). [5] Prochiral dienones are C 2 -symmetric molecules containing enantiotopic faces (ring surfaces) and enantiotopic groups (olefins and carbonyl group) that could provide four possible stereoisomers from conjugate addition reaction (Figure 2b). Enantioselective desymmetrization could generate enantioenriched products containing one or more stereocenters from C 2 -symmetric 2,5cyclohexadienones, which involves the differentiation of enantiotopic faces and groups with designed chiral catalysts or ligands.…”
Section: Introductionmentioning
confidence: 99%